Faktor-Faktor yang Mempengaruhi Inovasi Produk Koperasi Jasa Keuangan Syariah Pada KJKS BTM Se Jawa Tengah - Cholisa Rosanti (ITB AAS INDONESIA Surakarta, 2020)
This study has the aim to investigate and obtain empirical evidence Factors that affect product innovation Cooperative Financial Services Sharia At BTM KJKS of Central Java. The method used in this research is quantitative method is the method of the survey to the Manager / Branch Manager BTM KJKS of Central Java which has done more product innovation than five years. Which gained 35 respondents from 35 respondents there. This study uses SmartPLS assistance program version 2.0 as a test of the hypothesis that exist in this study. The results of this study are factors that affect product innovation Cooperative Financial Services Sharia At BTM KJKS of Central Java is fully proved empirically is the corporate culture and environment dynamics.